Characterization and Evaluation of Some Properties of Oleoresin from Capsicum Annuum Var. Cacho de Cabra [Caracterización y Evaluación de Algunas Propiedades de Oleorresina de Capsicum Annuum Var. Cacho de Cabra] - Matiacevich, S; Riquelme-Hinojosa, N (Taylor and Francis Ltd., 2017)
Oleoresin of Capsicum sp. is considered a food additive due to its color and pungency, and its active compound, capsaicin, is characterized by antimicrobial and antioxidant properties. However, Chilean variety of Capsicum sp. has not been characterized yet. The purpose of this study was to characterize the oleoresin of Capsicum annuum var. Cacho de cabra (OCc). Solvent extraction of OCc was carried out with hexane and physical properties of the OCc obtained were determined. Antimicrobial and antioxidant properties of OCc were compared with its active compound, capsaicin. Results showed that OCc has good optical properties compared with other commercial oleoresins and better antimicrobial properties than pure capsaicin. Due to the good optical properties obtained for OCc, this oleoresin could have a higher commercial value to be used as a coloring and flavor of various products, giving an added value to this variety of pepper. © 2016 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.